If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy + -4x + -6y = 0 Reorder the terms: -4x + xy + -6y = 0 Solving -4x + xy + -6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. -4x + xy + -6y + 6y = 0 + 6y Combine like terms: -6y + 6y = 0 -4x + xy + 0 = 0 + 6y -4x + xy = 0 + 6y Remove the zero: -4x + xy = 6y Combine like terms: 6y + -6y = 0 -4x + xy + -6y = 0 The solution to this equation could not be determined.
| L=500000-35000x | | 7(3x+2)=266 | | 10.5=y*1.05 | | 6(5x+3)=378 | | 10=y*1.05 | | 6x+4x+7=9 | | -11m-2=-9m | | 5+5=-6 | | m+m=-6 | | 3+3=-6 | | 2e^8x=75 | | 8=-x+2x-5x | | 6x+53=107 | | -1=5+-1 | | (x)(x)+8x+16=0 | | 8x-9y+3z=1 | | -k+2=-2 | | 3(k+5)=0 | | 1y+1=2 | | -23=16h-7+6h | | 16+-2=18 | | 2(4x-5)-4(1+3x)=12-3(x-1) | | 4(y-2)=-24 | | 500g=oh | | -8n=n-27 | | 500g= | | 9a^2+12a+24=0 | | -12n+9n=15 | | x^2-20x+119=0 | | x+(2x+21)= | | -n-8=-10 | | 2(3t+1)-8=t-(t+5) |